2018
DOI: 10.1002/chem.201804811
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐Borane Dehydrogenation and Transfer Hydrogenation Catalyzed by α‐Diimine Cobaltates

Abstract: Anionic α‐diimine cobalt complexes, such as [K(thf)1.5{(DippBIAN)Co(η4‐cod)}] (1; Dipp=2,6‐diisopropylphenyl, cod=1,5‐cyclooctadiene), catalyze the dehydrogenation of several amine‐boranes. Based on the excellent catalytic properties, an especially effective transfer hydrogenation protocol for challenging olefins, imines, and N‐heteroarenes was developed. NH3BH3 was used as a dihydrogen surrogate, which transferred up to two equivalents of H2 per NH3BH3. Detailed spectroscopic and mechanistic studies are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 104 publications
4
55
0
1
Order By: Relevance
“…First, average deuterium incorporation in the product was studied using different deuterated ammonia boranes and trifluoroethanols (cf. Table S7 in the Supporting Information) [34] . The results seem to indicate that the protic hydrogen from the solvent and the hydridic hydrogen from borane are primarily involved in the hydrogen transfer.…”
Section: Methodsmentioning
confidence: 92%
“…First, average deuterium incorporation in the product was studied using different deuterated ammonia boranes and trifluoroethanols (cf. Table S7 in the Supporting Information) [34] . The results seem to indicate that the protic hydrogen from the solvent and the hydridic hydrogen from borane are primarily involved in the hydrogen transfer.…”
Section: Methodsmentioning
confidence: 92%
“…Another example of TH and hydrogenation of olefins was reported by Wolf and co‐workers [37] . the authors used a catalytic amount of a reduced cobaltate anion [K(thf) 1.5 {( IPr BIAN)Co(COD)}] (BIAN=bis(iminoacenaphthene)diamine) to perform dehydrogenation of H 3 N⋅BH 3 , TH of disubstituted olefins and imines with H 3 N⋅BH 3 and hydrogenation of tri‐ and tetrasubstituted alkenes (Scheme 11).…”
Section: Catalyzed Classical Th Reactionsmentioning
confidence: 99%
“…The produced H 2 gas from AB dehydrogenation is released in situ, facilitating catalyst-mediated hydrogenation of an unsaturated compound. Co (II)-, Cu(I)-, Bi(I)-, Pd(II)-and borane catalysts dominate the field of catalytic TH of unsaturated compounds with AB as H 2 source, i. e. nitriles, [9] nitroarenes, [10] N-heteroaromatics, [11] alkynes, [12] alkenes, [11] imines, [13] and pyridines. [14] These reactions are, however, still limited to long reaction times, elevated temperatures and excessive amounts of AB.…”
mentioning
confidence: 99%
“…To our knowledge these conditions are the best reported for the TH of any substrate using AB operating under homogeneous conditions. Previous studies either required longer reaction times, [11] higher temperatures, [12c] more than 1 equivalent of AB [9a] or phosphine-containing ligands. [9a] Further evaluation revealed that no dehydrogenation of 1,2,3,4-tetrahydroquinoline was observed when 1,2,3,4-tetrahydroquinoline was added to a methanol/toluene solution of the pre-catalyst at elevated (110°C) temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation